2019
DOI: 10.1002/slct.201901551
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Quantum Dot as Electron Transporting Layer in Organic Light Emitting Diode

Abstract: Carbon quantum dots derived from banana leaves by a simple hydrothermal process has been used as an electron transport layer to fabricate Organic Light Emitting Diodes. To the best of our knowledge, this is the first report of Carbon QD utilized as an electron transport layer inOLED. Devices with multilayered structureITO/PEDOT: PSS/PFO/CQD/LiF/Al are fabricated on indium tin oxide (ITO) coated glass substrates. Current-Voltage (IÀ V) curves reveal that the turn-on voltages are reduced from 8 V to 6 V as compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Recently, Parmar and coworkers demonstrated that CDs could also be utilized as electron transport layer materials in fabricating LEDs. [ 97 ] The CDs with size of ≈4–6 nm were prepared from banana leaves via one step hydrothermal process. To confirm the electron transport ability of CDs, the authors prepared two LEDs with device structure of ITO/PEDOT:PSS/PFO/LiF/Al and ITO/PEDOT:PSS/PFO/CD/LiF/Al, respectively.…”
Section: Recent Advances In Cd‐based Electroluminescent Ledsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Parmar and coworkers demonstrated that CDs could also be utilized as electron transport layer materials in fabricating LEDs. [ 97 ] The CDs with size of ≈4–6 nm were prepared from banana leaves via one step hydrothermal process. To confirm the electron transport ability of CDs, the authors prepared two LEDs with device structure of ITO/PEDOT:PSS/PFO/LiF/Al and ITO/PEDOT:PSS/PFO/CD/LiF/Al, respectively.…”
Section: Recent Advances In Cd‐based Electroluminescent Ledsmentioning
confidence: 99%
“…The key to obtain solid‐state fluorescent CDs is to overcome or prevent AIQ effect. In the past few years, massive endeavors have been made to achieve solid‐state fluorescent CDs toward developing suitable CDs‐based composites by using polymers, [ 98–101 ] starch, [ 102 ] inorganic salt, [ 91–104 ] polyhedral oligomeric silsesquioxanes, [ 105 ] and silica [ 106,107 ] as matrices. However, only CDs in low loading fractions can lead to high QY in these situations.…”
Section: Research Opportunities For High Performance Cd‐based Electromentioning
confidence: 99%
“…Alam et al [83] reported the use of CDs synthesized with a one-step hydrothermal process using the banana leaf precursor as the ETL in direct architecture LEDs with polyfluorene derivative as the emitting layer (Figure 23a,b). The introduction of CD as the ETL reduces the energy barrier for electron injection, which in turn lowered the VON.…”
Section: Cds As Charge Regulating Interlayermentioning
confidence: 99%
“…Alam et al [89] reported the use of CDs synthesized with one step hydrothermal process using banana leaf precursor, as ETL in direct architecture LEDs with polyfluorene derivative as emitting layer (Fig.23a). The introduction of CD as ETL reduces the barrier for electron injection which in turn lowered the VON.…”
Section: Cds As Charge Regulating Interlayermentioning
confidence: 99%